Pharmacokinetic effect of disease severity and use of extracorporeal membrane oxygenation in critically ill Asian patients receiving vancomycin - Avachat, Charul; Hung, Pi-lien; Birnbaum, Angela K.; Healy, Daniel P.; Sherwin, Catherine M.; Lin, Alex C. (Frontiers in Pharmacology, 2025)
PurposeVancomycin is an essential antibiotic for the treatment of severe gram-positive bacterial infections, including methicillin-resistant Staphylococcus aureus (MRSA). In critically ill patients, particularly children, attaining the appropriate dosage is crucial to avert drug resistance and ensure therapeutic efficacy. This study sought to investigate the pharmacokinetics of vancomycin in critically ill Asian pediatric patients and evaluate the influence of extracorporeal membrane oxygenation (ECMO) and disease severity on vancomycin clearance.MethodsThis retrospective analysis examined data from 90 critically ill Asian patients residing in Kaohsiung, Taiwan, encompassing 263 data points gathered over 2 years. A one-compartment pharmacokinetic model with first-order elimination was constructed using nonlinear mixed-effects modeling to assess the impact of ECMO and infection severity on vancomycin clearance.ResultsThe pharmacokinetics of vancomycin were markedly affected by ECMO and the severity of the illness. Patients using ECMO demonstrated a 56% decrease in vancomycin clearance relative to non-ECMO patients. Furthermore, patients with milder infections (e.g., cellulitis, surgical prophylaxis, neutropenic fever) had a 39% decrease in vancomycin clearance relative to those with more severe infections (e.g., pneumonia, bacteremia, osteomyelitis, meningitis, deep tissue infection).ConclusionThe study demonstrates that ECMO and infection severity are major factors influencing vancomycin clearance in critically unwell pediatric patients. The significant decrease in clearance linked to ECMO and reduced infection severity underscores the necessity for meticulous therapeutic drug monitoring and tailored dosing strategies to enhance vancomycin treatment in this at-risk population. The findings highlight the significant interindividual diversity in vancomycin pharmacokinetics in critically unwell pediatric patients.